Challenging aspects of contemporary cochlear implant electrode array design - Pavel Mistrík (KeAi Communications Co., Ltd., 2017)
Objective: A design comparison of current perimodiolar and lateral wall electrode arrays of the cochlear implant (CI) is provided. The focus is on functional features such as acoustic frequency coverage and tonotopic mapping, battery consumption and dynamic range. A traumacity of their insertion is also evaluated. Methods: Review of up-to-date literature. Results: Perimodiolar electrode arrays are positioned in the basal turn of the cochlea near the modiolus. They are designed to initiate the action potential in the proximity to the neural soma located in spiral ganglion. On the other hand, lateral wall electrode arrays can be inserted deeper inside the cochlea, as they are located along the lateral wall and such insertion trajectory is less traumatic. This class of arrays targets primarily surviving neural peripheral processes. Due to their larger insertion depth, lateral wall arrays can deliver lower acoustic frequencies in manner better corresponding to cochlear tonotopicity. In fact, spiral ganglion sections containing auditory nerve fibres tuned to low acoustic frequencies are located deeper than 1 and half turn inside the cochlea. For this reason, a significant frequency mismatch might be occurring for apical electrodes in perimodiolar arrays, detrimental to speech perception. Tonal languages such as Mandarin might be therefore better treated with lateral wall arrays. On the other hand, closer proximity to target tissue results in lower psychophysical threshold levels for perimodiolar arrays. However, the maximal comfort level is also lower, paradoxically resulting in narrower dynamic range than that of lateral wall arrays. Battery consumption is comparable for both types of arrays. Conclusions: Lateral wall arrays are less likely to cause trauma to cochlear structures. As the current trend in cochlear implantation is the maximal protection of residual acoustic hearing, the lateral wall arrays seem more suitable for hearing preservation CI surgeries. Future development could focus on combining the advantages of both types: perimodiolar location in the basal turn extended to lateral wall location for higher turn locations. Keyword: Cochlear implant